A Novel Global Key-Value Storage System Based on Kinetic Drives - Xiang Cao; Cheng Li (Algorithms, 2020)
NoSQL databases are flexible and efficient for many data intensive applications, and the key-value store is one of them. In recent years, a new Ethernet accessed disk drive called the “Kinetic Drive” was developed by Seagate. This new Kinetic Drive is specially designed for key-value stores. Users can directly access data with a Kinetic Drive via its IP address without going through a storage server/layer. With this new innovation, the storage stack and architectures of key-value store systems have been greatly changed. In this paper, we propose a novel global key-value store system based on Kinetic Drives. We explore data management issues including data access, key indexing, data backup, and recovery. We offer scalable solutions with small storage overhead. The performance evaluation shows that our location-aware design and backup approach can reduce the average distance traveled for data access requests.